2012
DOI: 10.1177/0022429411435363
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Positive Mindset Trigger Word Pre-Performance Routine on the Expressive Performance of Junior High Age Singers

Abstract: The effects of a positive mindset trigger word intervention on the expressive performance of individual junior high singers were tested in this study. Participants ( N = 155) were assigned randomly to a control group or an experimental group. Members of the experimental group participated in a 40-min intervention while members of the control group participated in normal rehearsal. The intervention involved a pre-performance routine of breathing and silently repeating the words bold, confident, and free. It als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…A few experimental studies compared methods for improving teenagers' expressiveness. Broomhead et al (2012Broomhead et al ( , 2018 reported that boosting confidence during pre-performance routines facilitated teenagers' expressiveness in singing. Chester (2008) compared aural modeling, concrete verbal instruction, metaphors, and no instruction, but found no significant differences between these methods.…”
Section: Background: Teaching Young Musicians Performance Expressionmentioning
confidence: 99%
“…A few experimental studies compared methods for improving teenagers' expressiveness. Broomhead et al (2012Broomhead et al ( , 2018 reported that boosting confidence during pre-performance routines facilitated teenagers' expressiveness in singing. Chester (2008) compared aural modeling, concrete verbal instruction, metaphors, and no instruction, but found no significant differences between these methods.…”
Section: Background: Teaching Young Musicians Performance Expressionmentioning
confidence: 99%
“…For example, Fritz and Avsec ( 2007 ) reported that when undergraduate music students experienced flow during their music practice, this was linked to increases in positive emotions and life satisfaction. Broomhead et al ( 2012 ) tested the effect of a PP teaching technique on the expressive performance of 155 junior high singers. The PP intervention involved a pre-performance routine of breathing and silent repetition of the words “bold”, “confident”, and “free”.…”
Section: The Capacity For Music Education To Boost Student Well-beingmentioning
confidence: 99%
“…This statistically reliable measurement tool has been used by judges to score one of seven levels of expressiveness within six sub-categories: timing, dynamics, articulation, performance factors, articulation, and style (Broomhead, 2009;Broomhead, Skidmore, Eggett, & Mills, 2012). This can be the closest standardized tool for measuring specific acoustical music factors of expressivity within a performance.…”
Section: Music Performance Expression Rating Measurement Toolsmentioning
confidence: 99%
“…Broomhead, Skidmore, Eggett, and Mills (2012) took the trigger word concept and applied it as an approach toward an expressive performance. In this study, junior high singers (N = 155) were divided into two separate groups.…”
Section: Metaphors and Guided Imagerymentioning
confidence: 99%